Black Tea Theaflavin Detoxifies Metabolic Toxins in the Intestinal Tract of Mice - Zhang, Shuwei (Mol Nutr Food Res, 2021)
SCOPE: The goal of this study was to determine the in vivo efficacy of theaflavin (TF), one of the major bioactive components in black tea, to detoxify two major metabolic toxins, ammonia and methylglyoxal (MGO), in mice. METHODS AND RESULTS: Under in vitro conditions, TF was able to react with ammonia, methylglyoxal (MGO), and hydrogen peroxide (H(2)O(2)) to produce its aminated, MGO conjugated, and oxidized products, respectively. In TF-treated mice, the aminated TF, the MGO conjugates of TF and aminated TF, and the oxidized TF were searched using LC-MS/MS. Our results provided the first in vivo evidence that the unabsorbed TF was able to trap ammonia to form the aminated TF; furthermore, both TF and the aminated TF had the capacity to trap MGO to generate the corresponding mono-MGO conjugates. Moreover, TF was oxidized to dehydrotheaflavin, which underwent further amination in the gut. By exposing TF to germ-free (GF) mice and conventionalized mice (GF mice colonized with specific-pathogen-free microbiota), the gut microbiota was demonstrated to facilitate the amination and MGO conjugation of TF. CONCLUSION: TF has the capacity to remove the endogenous metabolic toxins through oxidation, amination, and MGO conjugation in the intestinal tract, which could potentially explain why TF still generates in vivo efficacy while showing a poor systematic bioavailability.